2023
DOI: 10.1371/journal.pone.0286099
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure analysis in cultivated soybean (Glycine max [L.] Merr.) using SSR and EST-SSR markers

Abstract: Soybean (Glycine max) is an important legume that is used to fulfill the need of protein and oil of large number of population across the world. There are large numbers of soybean germplasm present in the USDA germplasm resources. Finding and understanding genetically diverse germplasm is a top priority for crop improvement programs. The current study used 20 functional EST-SSR and 80 SSR markers to characterize 96 soybean accessions from diverse geographic backgrounds. Ninety-six of the 100 markers were polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…The average PIC for the 25 SSRs studied was 0.625, indicating a high polymorphic level. Among twenty-five SSRs, Satt371, Satt243, Satt244, Satt458, and Sat288 were previously successfully used to assess genetic diversity in different soybean collections [55][56][57][58][59]. The results showed that only five SSRs were required to distinguish all nineteen accessions from Kazakhstan (Figure S2, which is comparable with reports using other crops [60].…”
Section: Analysis Of Population Structure and Polymorphism Level In T...supporting
confidence: 70%
“…The average PIC for the 25 SSRs studied was 0.625, indicating a high polymorphic level. Among twenty-five SSRs, Satt371, Satt243, Satt244, Satt458, and Sat288 were previously successfully used to assess genetic diversity in different soybean collections [55][56][57][58][59]. The results showed that only five SSRs were required to distinguish all nineteen accessions from Kazakhstan (Figure S2, which is comparable with reports using other crops [60].…”
Section: Analysis Of Population Structure and Polymorphism Level In T...supporting
confidence: 70%
“…Q1 contained most of the R-lines (pollinators), while Q2 possessed all Blines except for one R-line (Fig 3A and 3B). Individuals with a score for clusters membership coefficient more than 0.80 are considered as pure, while those who scored less than 0.80 was considered as admixture [41,42]. In the case of the R-lines cluster (Q1), 67 accessions were identified, out of which 58 were pure and nine were admixtures.…”
Section: Bayesian Model-based Population Stratificationmentioning
confidence: 99%
“…In addition to being used for genetic diversity analysis [12], molecular markers can also be used in gene mapping analysis [34,35], fingerprinting analysis [36], and mutant gene detection [37]. The use of molecular markers in soybean genetic diversity analysis was carried out in previous studies including Rani et al [38] on 96 soybean accessions with 96 SSR and EST-SSR markers, Jain et al [39] on 24 soybean genotypes with 18 RAPD markers, Sulistyo et al [40] on 40 soybean accessions with 13 SSR markers, Slamet et al [41] on 40 soybean genotypes using 20 SSR markers, and Agam et al [42] on 11 mutant soybean genotypes with 12 RAPD markers.…”
Section: Introductionmentioning
confidence: 99%